E-Commerce and the taxation in South Africa of non-residents - Zondo, Pumla (My University, 2017)
Technological advancements have introduced new methods of operating and transacting between business and targeted markets. Electronic interaction by business with respective target markets has enabled business to transact from any location around the world, instantaneously delivering goods and services to markets globally. Although benefits have been derived by business, the impact of e-commerce on established income tax principles has raised concern to governments around the world, as e-commerce grows as a method of transacting with targeted markets (Hubbard: 2016). Transacting in a digital environment has posed challenges to the taxation of residents and non-residents in South Africa which has resulted in the avoidance of income tax by taxpayers in countries of operation. Losses in tax revenue resulting from business conducted in e-commerce have been experienced (OECD, 2014a:5) by governments, as the application of income tax legislation is challenged by business operations in e-commerce (OECD, 2015:5). Transacting in a digital environment has provided business with the ability to operate in a market in the absence of physical premises established in that market, challenging income tax principles which rely on an association with a physical place or presence of an entity for taxation. This research report analyses the taxation of non-resident business operations in e-commerce in South Africa and the arising challenges due to ecommerce. An examination of the income tax legislation is performed to understand how tax is avoided by non-residents when operating in e-commerce. The possible solutions to address challenges posed to income tax by e-commerce will be examined as part of the research report. Keywords: BEPS; double tax agreements; e-commerce; income tax; non-residents; resident; source; permanent establishment.
A research report submitted to the Faculty of Commerce, Law and Management in partial fulfilment of the requirements for the degree of Master of Commerce (Taxation). Johannesburg, April 2017.
Keywords: Double taxation--South Africa; Taxation--Law and legislation--South Africa; Business enterprises, Foreign--Taxation--South Africa; International business enterprises--Taxation